Development of a Non-Textbook on Biodiversity in Sumatra Based on the Sustainable Development Goals to Improve Critical Thinking and Problem-Solving Skills - Tagonna E. Siburian; Ely Djulia; Widya Arwita (Jurnal Perspektif, 2026)
This study aims to create a non-textbook on SDGs-based biodiversity in Sumatra with practical applications that improve students' critical thinking and problem-solving skills. This ADDIE-based development research involved two classes of grade X students at SMA Negeri 1 Paranginan: experimental and control. Independent-samples t-tests were used to assess the feasibility, practicality, and effectiveness of the research data. This study found that the non-textbook on SDGs-based biodiversity in Sumatra is playful, practical, and effective in developing critical thinking and problem-solving skills of grade X students of SMA Negeri 1 Paranginan. Feasibility was met based on validation results from materials (80.0%), learning (89.3%), and media/design experts (78.7%), indicating feasibility. The biology instructor’s response questionnaire (83.6%) and the student's response questionnaire (76.2%) indicated a practical orientation. The evaluation results showed effectiveness, with N-gain values of 75.7% for critical thinking skills and 65.5% for problem-solving skills in the experimental class. Hypothesis testing confirmed the effectiveness (Sig.= 0.000 < 0.05) and (Sig.= 0.007 < 0.05).